Kemampuan Komponen Arus Kas Operasi Metode Langsung Dalam Memprediksi Arus Kas dan Dividen Masa Depan Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2018-2021 - Ni Kadek A; Elin Erlina S; Robith Hudaya (Magister Ilmu Akuntansi Universitas Jambi, 2023)
This research is associative research with a quantitative approach which aims to analyze the ability of the direct method operating cash flow components in predicting future cash flows and dividends in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021 period. The samples used in this study were 32 companies. Sampling used technique purposive sampling. The analytical method used is panel data regression. The data is tested using software Eviews 10. Operating cash flow proxied by cash inflows and cash outflows had a significant impact on predicting future cash flows in the first model study, as evidenced by partial testing with the t test. However, the second model study's findings demonstrate that operating cash flow, as proxied by cash inflows and cash outflows, has no significant impact on predicting future dividends.